Legume decomposition and nitrogen release when applied as green manures to tropical vegetable production systems - Th o ¨ nnissen, Carmen; Midmore, David J.; Ladha, Jagdish K.; Olk, Daniel C.; Schmidhalter, Urs (Wiley, 2000)
For legume green manures (GM) to be effective, environmentally sound N sources for horticultural crops in the tropics, their N release must be in synchrony with crop N demand. Decomposition and N release of surface applied (mulch) or incorporated soybean [Glycine max (L.) Merr.] and indigofera (Indigofera tinctoria L.) GM were studied in six field studies conducted at three locations in Taiwan and the Philippines between 1993 and 1995. Litter bags and inorganic N soil samplings were used in order to understand tomato (Lycopersicon esculentum Mill.) crop responses to GM N. Resulting soil N contents were compared with a control (no GM, no fertilizer). The N content of 60 to 74 d soybean GM varied between 110 and 140 kg N ha−1 and that of indigofera between 5 and 40 kg N ha−1. Nitrogen‐15‐labeled soybean GM was traced in the soil and in organic matter fractions (humic acids, calcium humates, humins) in one of the field studies. Soybean and indigofera decomposed rapidly, losing 30 to 70% of their biomass within 5 wk after application, depending on GM placement, season (wet vs. dry), and location. Soil nitrate contents increased corresponding to GM N release at all locations and seasons, with a maximum increase of 80 to 100 kg NO3–N ha−1 with incorporated soybean. The peak N release occurred 2 to 6 wk after GM application in two of the three locations, and 5 to 8 wk in the third location. The apparent decline of GM N release at all locations and seasons 8 wk after application was only partly caused by tomato N uptake. At tomato harvest, 30 to 60% of the GM 15N was found in the soil, and was found mostly in humins. Comparable N release dynamics across seasons and locations suggest a possible N fertilizer substitution by incorporated soybean GM for basal N application and first side dressing to tomato. With respect to season and location, GM N should be supplemented with N fertilizer starting after 8 wk to ensure optimal tomato yields.